The leaderships role in education of the federal inspector of the schools as perceived by inspectors themselves and teachers in selected primary and secondary schools in Negri Sembilan / Sergit Singh Gurbakah Singh - Sergit Singh, Gurbaksh Singh (1974)
The Objective of the study was to obtain an insight into the present functions and powers of Inspectors of Schools as perceived by Inspectors and teachers in selected Primary and Secondary Malay and English medium schools in Negeri Sembilan. The Investigation was primarily concerned with the setting in which The Inspectors works-his functions and work load and the distribution of his time among various responsibility areas. Of particular concern in the study was the advisory and guidance function of Inspectors of Schools which may be viewed as directly related to the Inspector’s staff leadership role. The views of Inspectors and teachers on the effectiveness of his performances and on problems and hindrances relating to educational inspection were also determined. The Inspector’s leadership role in education was examined in terms of relevant information found in the literature on educational inspection and supervision. In conducting the study, an examination was made of Sections 92-96 of the Education Ordinance 1957 which relate to the duties of Inspectors of Schools. The major source of information, however, were the questionnaires which were completed by 28 Federal Inspectors of Schools and 244 teachers in the state of Negeri Sembilan. The findings indicate that the legal status of the Inspector needs some clarification, especially with respect to the Inspector’s leadership role. The findings also indicate that a little more 50% of teachers did not perceive the Inspector’s role as primarily that of giving advice and guidance to teachers. The study also showed up that the large number of the staff personnel in the state in relation to the numbers of Inspectors makes the task of providing adequate professional guidance to the teachers a difficult one to perform without assistance. The four most important recommendations arising out of the study are: (1) the Ministry of Education initiate a revision of the Education Ordinance 1957 for the purpose of defining what the advisory and executive functions entail; (2) the number of appointments in the Federal Inspectors of Schools be increased if Inspector’s services are to be effective and efficient; (3) the ministry of Educations should consider assisting Inspectors to obtain higher qualifications by making such provision as study leave or attendance at university or other relevant courses, and (4) the establishment of closer liason between Inspectors and teachers’ colleges out of the which fuller understand-ding of the each other’s tasks, problems and potentialities can develop.